Review on Data Securing Techniques for Internet of Medical Things - Kanthavel, R. (Journal of Soft Computing Paradigm, 2021)
In recent days Internet of Things (IOT) has grown up dramatically. It has wide range of applications. One of its applications is Health care system. IOT helps in managing and optimizing of healthcare system. Though it helps in all ways it also brings security problem in account. There is lot of privacy issues aroused due to IOT. In some cases it leads to risk the patient’s life. To overcome this issue we need an architecture named Internet of Medical Things (IOMT). In this paper we have discussed the problems faced by healthcare system and the authentication approaches used by Internet of Medical Things. Machine learning approaches are used to improvise the system performance.
Keywords: Internet of Things (IOT); healthcare system; Internet of Medical Things (IOMT); authentication; machine learning